(untitled) (Universal International Scientific Journal, 2026)
This article is an attempt to investigate the relationship between the gender of a translator and the gender of the evaluator of the work of that translator. The researcher hypothesizes that if a male rater is to evaluate a translated text done by both a man and a woman, he would unconsciously choose the translation of the same gender and vice versa. To test this hypothesis, 6o (30 men and 30 women) senior students of the translation training program at the Maritime University of Chabahar were selected and participated in the experiment. The test included 20 questions; it was designed based on two translations of one chapter of a short story which was translated one by a male and the other by a female translator from English to Persian. Two of the answer options were the translations of the two translators and the others were wrong translations. The subjects were asked to choose just the one which was nearest to their own opinions.